2009
DOI: 10.1093/toxsci/kfp257
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Transfer and Metabolism in Human Placenta

Abstract: Aflatoxin B1 (AFB1), a common dietary contaminant, is a major risk factor of hepatocellular carcinoma (HCC). Early onset of HCC in some countries in Africa and South-East Asia indicates the importance of early life exposure. Placenta is the primary route for various compounds, both nutrients and toxins, from the mother to the fetal circulation. Furthermore, placenta contains enzymes for xenobiotic metabolism. AFB1, AFB1-metabolites, and AFB1-albumin adducts have been detected in cord blood of babies after mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…The AFB1 itself is not a potent toxin, and the bioactivation by liver CYP450 enzymes (Yen et al, 2009), particularly CYP3A4 and CYP1A2 to AFB1-8,9-epoxide, can form adducts with DNA and protein albumin (Partanen et al, 2010;Polychronaki et al, 2008), where its toxicity and carcinogenic effects are evident (Eaton and Gallagher, 1994). Although the AFB1 DNA adduct is more relevant with the HCC, we used AFB1 albumin adducts as biomarkers to assess the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The AFB1 itself is not a potent toxin, and the bioactivation by liver CYP450 enzymes (Yen et al, 2009), particularly CYP3A4 and CYP1A2 to AFB1-8,9-epoxide, can form adducts with DNA and protein albumin (Partanen et al, 2010;Polychronaki et al, 2008), where its toxicity and carcinogenic effects are evident (Eaton and Gallagher, 1994). Although the AFB1 DNA adduct is more relevant with the HCC, we used AFB1 albumin adducts as biomarkers to assess the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommended the reduction of the AFLAM 1 levels in milk and dairy products to a minimum, in order to minimize the potential risk it poses. The toxic and carcinogenic effects have been extensively demonstrated in several species, especially in young animals [6,7]. There is, therefore, a great concern regarding the health of children, considering their high consumption of milk and dairy products, their low body weight and their great susceptibility to aflatoxins [5].…”
Section: Introductionmentioning
confidence: 99%
“…The toxin given perorally is absorbed rapidly into the system of pregnant mice [3]. By perfusing the placenta after delivery, Partanen et al have demonstrated that aflatoxin B1 could pass through the organ and enter the fetal circulation [24]. These studies indicate that the toxin can be absorbed and transported across the placental tissue during pregnancy.…”
Section: Discussionmentioning
confidence: 99%